Social Innovation Education and Social Innovation Skill Development - Garefi, Ioanna; Kalemaki, Irene; Schorer, Antonia; Protopsaltis, Aristidis (ICERI2020 Proceedings, 2020)
Social Innovation Education (SIE) is a new educational concept that is different from Entrepreneurship Education (EE), Citizenship Education (CE) and Education for Sustainable Development (ESD). SIE is a collaborative and collective learning process for the empowerment and socio/political activation of students to drive positive change no matter their professional pathways. SIE builds students’ competences to identify opportunities for social value creation, to form collaborations and build relationships and take innovative action for a more democratic and sustainable society [1]. Its effect on learning has a threefold objective, to empower students by actively engaging them as co-creators of their learning activities, to socio-politically activate them to drive social change and finally, to develop the necessary competences for a more democratic and sustainable society. In the context of the NEMESIS Horizon2020 project, a Social Innovation Learning Framework (SILF) was developed together with a social innovation competence framework containing 14 competences, with 4 levels of development [1]. The emphasis of the social innovation competences is placed on the collective ability to identify opportunities and take action alongside individual abilities to form relationships and participate effectively in collaborative learning and decision-making. The social innovation competence framework was evaluated as part of the SILF in a yearlong pilot study, in 5 European countries. A realistic evaluation approach was employed to evaluate how students were impacted and how their competences were developed by their involvement in the design, co-creation and implementation of social innovation projects. 56 teachers, 1030 students and 69 local community actors from 5 different European countries (GR, FR, ES, PT, UK) took part in the evaluation. However, 206 students have participated in the post-assessment survey regarding the competences and the results presented here have also taken into account the feedback from teachers, Social Innovation Practitioners (SIP) and parents. The majority of the results have shown a positive impact of SIE on social innovation competence development with many students progressing through different level of competences and becoming more socially aware and competent. For instance, regarding the competence “vision for a better world” Greek students indicated that their level of competence progression they indicated that they have reached a level 3 (41%) whereby Spanish students reached level 4 (42%), both from level 2. In both cases, the results revealed that SIE helped their social innovation competence development in significant way. Similarly, for the “social resilience” competence 39% of Greek students and 25% of Spanish students indicated reaching Level 3, while 38% of Greek students and 31% of Spanish indicated reaching Level 4. 23% of Spanish students and 7% of Greeks were still at Level 1 and 21% and 15% of Spanish and Greek students respectively reached Level 2. Similar results were revealed for most of the other competences. Finally, the results revealed that assessing the level or progress of competence development is indeed an ongoing process in which knowledge and skills are continually built. It is not something that can be harnessed in a short-term period but something that needs continuous efforts.<br
Keywords: innovation; social innovation; social innovation education